Detecção de Theileria equi por reação em cadeia da polimerase em amostras de sangue de equinos no Rio Grande do Sul - Rodrigues, Daniele (2018)
Theileria equi is a protozoan of the class Piroplasmasida of the phylum Apicomplexa, which needs a vector tick for transmission of Piroplasmosis, which can be asymptomatic or present in a severe form, causing severe anemia, decreased performance and death in horses. Since one of the pillars of the Rio Grande do Sul (RS) economy is equine activity, the objective of this work was to determine by polymerase chain reaction (PCR) the occurrence of Theileria equi in equine blood samples sent to the cell blood count (CBC), to the laboratory of clinical analyzes of the University Veterinary Hospital of Santa Maria. DNA from 144 whole blood samples from horses was analyzed. The phenol-chloroform method was used for the extraction and amplification was performed with specific primers for the agent, according to the literature. Samples of 53 horses were positive for Theileria equi. The use of PCR for the diagnosis of equine piroplasmosis has shown to be a technique with high specificity and sensitivity that can be offered as a diagnostic method in the laboratory of clinical analyzes of the UFSM veterinary hospital.